Fate of emerging contaminants in the soil-plant system: a study on durum wheat irrigated with treated municipal wastewater - Denora, Michele; Mehmeti, Andi; Candido, Vincenzo; Brunetti, Gennaro; De Mastro, Francesco; Murgolo, Sapia; De Ceglie, Cristina; Gatta, Giuseppe; Giuliani, Marcella Michela; Fiorentino, Costanza; Perniola, Michele (Frontiers in Soil Science, 2024)
Emerging contaminants in irrigation wastewater can cause bioaccumulation in crops, posing health risks to humans and other living organisms. The extent to which different emerging contaminants (ECs) are taken up by plants varies depending on the physicochemical properties of the contaminants and the type of crops grown. This study investigated the fate of emerging contaminants (ECs), particularly pharmaceuticals, in durum wheat grown on soils irrigated with treated wastewater in southern Italy. The experiment was conducted in lysimeters irrigated with wastewater during previous crop cycles, assessing the presence and distribution of ECs in both soil and plant tissues. Three different levels of exposure to ECs were compared: freshwater irrigation (FW), wastewater treated to European average contaminant levels (TWWx1), and a triple dose of contaminants (TWWx3). The behavior of 12 different ECs in the plant-soil complex was analyzed and found variable. Fluconazole and carbamazepine were found to have higher uptake concentrations in the plant, with accumulation observed in the plant and grain, especially in the TWWx3 treatment. However, some ECs (such as Sulfamethoxazole, Trimethoprim, Ketoprofen, Diclofenac, Metoprolol, and Naproxen) showed high uncertainties in their fate, probably due to degradation in soil and influential crop parameters. The results of this study contribute to the argument that the reuse of treated wastewater for irrigation, if properly monitored, can be a safe approach in agriculture and can support policymakers in developing future legislative frameworks for sustainable water management.